PENDAMPINGAN KADER KESEHATAN MENINGKATKAN BERAT BADAN DAN MENCEGAH KEKURANGAN ENERGI KRONIS (KEK) IBU HAMIL TRIMESTER II - Hodikoh, Atik; Surtiati, Eti; Yumi, Hilmi; Meirina, Meirina (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2025)
Chronic Energy Deficiency (CED) is a condition of the mother who experiences a lack of energy and protein that lasts for many years (chronic) which is characterized by Upper Arm Circumference (MUAC)<23.5 cm and looks thin. Women with MUAC<23,5 cm are at risk of giving birth to children with Intra Uterine Growth Retardation (IUGR), Low Birth Weight (LBW), and stunting. The prevalence of pregnant women in SEZs in 2023 is 16.9%. Efforts need to be made to improve the nutritional status of pregnant women with SEZs, including providing nutrition education, monitoring pregnant women’ health, and assistance by health cadres. The study aimed to determine the effect of health cadre assistance on weight and prevention of CED in second-trimester pregnant women. The research method used was Quasi experiment with control group. The sample was 58 second-trimester pregnant women in the intervention group and 60 pregnant women in the control group. The analyses that will be used independent sample t-tests, and paired t-tests. The results showed increase in the value of knowledge by 24.7(intervention group) and 1.24(control group). There was an increase in attitude values 1.09 in intervention group and 0.45 in control group. The weight gain in the intervention group was 0.31 kg greater than the control group and there was an increase in MUAC in the intervention group of 0.79 cm. It can be concluded that there was a significant influence on the weight (p=0.033), LILA (0.047), attitude and knowledge(p=0.072) of second-trimester pregnant women after being assisted by health cadres.